Qualitative aspects of the carcass and ovine meat are modified with the use of water spray - Mateus, Karina Aline; Santos, Moisés Rodrigues dos; Chiocca, Maisa; Lima, Jocelita de; Orso, Tálison; Cucco, Diego de Córdova; Kessler, Julcemar Dias (Revista de Ciências Agroveterinárias, 2019)
The objective of this research was to investigate the qualitative aspects of sheep meat, after the submission or not of 20 carcasses to water spray. The experiment was carried out in a randomized block design, with two treatments with ten carcasses each and ten replicates. The carcasses were submitted and not submitted to water sprinkling for 10 consecutive hours in a cold chamber. Instrumental meat quality analyzes were performed on the Longissimus thoracis et lumborum (LTL) muscles, and occurred in two distinct periods, initially within the 24-hour post-mortem period and after 7 months of non-industrial freezing. The pH, meat and subcutaneous fat staining, cooking loss, water retention capacity, water activity, sarcomere length, shear force and body measurements of the carcass were analyzed. In addition to these, subjective color and marbling measurements and microbiological analysis (Escherichia coli) were included. After the analysis, it was observed that sputum carcasses, LTL muscle modified chroma within 24 hours post mortem and tonality after freezing (7 months). In addition, there was an increase in the microbiological count (5.9 x 10¹ and 4.3 x 10² UFC / cm²) and in the refrigerator yield (48.77, 46.28 kg). However, there was greater loss in cooling (4.87, 3.27%). And in for unprosted carcasses, there was a greater decline in pH 2 hours post mortem (pH 6.9) and lower final pH after 24 hours (pH 5.6). However, after freezing there was no significant difference (p<0.05) between treatments. For the other analyzes, no significant difference was found. The use or not of spraying for 10 consecutive hours in ovine carcasses, promotes unwanted changes in the qualitative aspects of the carcass and meat. In this sense, we do not recommend prolonged use (10 hours) of spraying on ovine carcasses.